1983
DOI: 10.1007/bf02482643
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin III (AT III) Padua2: A “New” congenital abnormality with defective heparin co-factor activities but no thrombotic disease

Abstract: A "new" antithrombin III (AT III) abnormality is described in five members of the same family. None of the affected members showed thrombotic manifestations and no consanguinity was present in the family. The main laboratory features were: normal routine clotting tests, slightly decreased AT III activities in all assays carried out in the presence of heparin. In the absence of heparin, antithrombin III activities were instead within normal limitis. Progressive AT III activity and AT III antigen were also norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…3 Inhibition of thrombin and of activated factor X by normal (N) and propositus (P) plasma in absence (A) and in presence (B) of heparin minutes been described. In three of them no thromboembolic disorder was found (2,5,8). In the four other similar variants published, only one rnember per family experienced thrombosis (3,4,6,9) and moreover two were homozygous (6,9).…”
Section: Discussionmentioning
confidence: 83%
“…3 Inhibition of thrombin and of activated factor X by normal (N) and propositus (P) plasma in absence (A) and in presence (B) of heparin minutes been described. In three of them no thromboembolic disorder was found (2,5,8). In the four other similar variants published, only one rnember per family experienced thrombosis (3,4,6,9) and moreover two were homozygous (6,9).…”
Section: Discussionmentioning
confidence: 83%
“…CIE of normal plasma gave 1 high, fast moving peak, followed by 2 small, slow-moving peaks Padua (15) Padua 2 (16) Toyama (17) Ann Arbor (18) Aalborg (19) Chicago (20) Vicenza (21) Milan ( position roughly corresponding to that of the 1st of the slow-moving peaks in normal plasma (Figure 1C).…”
Section: Resultsmentioning
confidence: 96%
“…Nevertheless, it has been suggested that heterozygous patients with variant antithrombin molecules, particularly type III, have fewer thromboembolic complications. [46][47][48] In these families, thrombosis has occurred only in homozygous persons.…”
Section: Subtypes Of Inherited Antithrombin Deficiencymentioning
confidence: 99%